2006
DOI: 10.1038/sj.onc.1209685
|View full text |Cite
|
Sign up to set email alerts
|

HER2 signaling modulates the equilibrium between pro- and antiangiogenic factors via distinct pathways: implications for HER2-targeted antibody therapy

Abstract: We determined the impact of HER2 signaling on two proangiogenic factors, vascular endothelial growth factor (VEGF) and interleukin-8 (IL-8), and on an antiangiogenic factor, thrombospondin-1 (TSP-1). Re-expression of HER2 in MCF-7 and T-47D breast cancer cells that endogenously express low levels of HER2 resulted in elevated expression of VEGF and IL-8 and decreased expression of TSP-1. Inhibition of HER2 with a humanized anti-HER2 antibody (trastuzumab, or Herceptin s ) or a retrovirus-mediated small interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
132
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(142 citation statements)
references
References 51 publications
6
132
0
4
Order By: Relevance
“…It has been reported that inhibition of HER2 can activate p38 MAPK, which in turn stimulates TSP-1 expression. 9 Because T/t-common can inhibit HER2, we thus tested whether T/t-common could stimulate the activity of p38 MAPK in SK-OV-3 cells. As shown in Figure 5f, compared with mock-or rAd-V-infected SK-OV-3 cells, the level of phospho-p38 was significantly increased in rAd-T/t-infected SK-OV-3 cells, and the level of total p38 protein was not altered in these cells.…”
Section: Inhibition Of Angiogenesis By Sv40 T/t-common S-p Hsueh Et Almentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that inhibition of HER2 can activate p38 MAPK, which in turn stimulates TSP-1 expression. 9 Because T/t-common can inhibit HER2, we thus tested whether T/t-common could stimulate the activity of p38 MAPK in SK-OV-3 cells. As shown in Figure 5f, compared with mock-or rAd-V-infected SK-OV-3 cells, the level of phospho-p38 was significantly increased in rAd-T/t-infected SK-OV-3 cells, and the level of total p38 protein was not altered in these cells.…”
Section: Inhibition Of Angiogenesis By Sv40 T/t-common S-p Hsueh Et Almentioning
confidence: 99%
“…2,7 Preclinical data show that HER2 activation contributes more to the oncogenic phenotype than any of the other HER receptors. 3,8 In fact, overexpression of HER2 has been shown to be correlated with poor prognosis, 4,5 increased angiogenesis, 5,9 enhanced metastatic potential 5,10 and increased chemoresistance of human cancers. 5,11 Angiogenesis is the formation of new blood vessels from existent microvessels and is required for physiological and pathological processes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations